National History: Construct or/and Reality? - Historein, Historein (Historein, 2000)
A workshop addressing the general theme “National History. Construct or/and Reality” was held at the European University Institute (Florence) on the 2nd and 3rd of May 1997. Professor Miroslav Hroch (European University Institute and University of Prague) organised and conducted this project which aimed at a comparative approach of the formation of national histories mostly within Central and Eastern Europe. The first two sessions (Friday, May 2nd, morning and afternoon) were devoted to the exploration of “The Concept of our National History”. The following scholars (according to the order of presentation) focused their analysis on certain cases of national histories: A. First session - Professor Otto Dann (University of Köln) - Germans. - Professor Miroslav Hroch (EUI and University of Prague) and Dr. Jitka Maleckova (University of Prague) - Czechs. - Professor Ottar Dahl (University of Oslo) - Norwegians. - Professor Marjatta Hietala (University of Tampere) - Finns. B. Second session - Dr. Eva Ring Agh (University of Budapest) - Hungarians. - Dr. Bronislav Hronec (University of Bratislava) - Slovaks. - Dr. Effi Gazi (University of Crete) - Greeks.